A computational approach for the solution of the MHD and thermal flow of a liquid metal between two horizontal concentric cylinders. (1st January 2014) - Hatzikonstantinou, P.M.; Bakalis, P.A.
The purpose of this paper is to study the fully developed laminar magnetohydrodynamic (MHD) and thermal flow of an electrically conducting liquid metal between two horizontal concentric cylinders, maintained at uniform temperatures, under the effect of an external transverse magnetic field. The temperature difference between the walls creates buoyancy force, due to density variations. Three different models are compared for the solution of the electromagnetic variables. The φ-formulation, based on the electric potential equation, the b-formulation, based on the induced magnetic field and the hybrid h-formulation. A numerical method, based on the continuity vorticity pressure (CVP) variational method, is used for the coupling of the magnetohydrodynamic equations.